Regenerative endodontic therapy using platelet-rich fibrin in children - Parul Singhal; Bindu Kadian; Pawan Midha; Ritu Namdev (Wolters Kluwer Medknow Publications, 2020)
Regeneration of pulp-dentin complex in an infected necrotic tooth with an open apex is possible if the canal is effectively disinfected. The purpose of this case report is to add regenerative endodontic cases to the existing literature about the use of plateletrich fibrin (PRF). Three clinically and radiographically diagnosed necrotic immature permanent teeth were treated using PRF as a scaffold for revascularization. The therapeutic protocol involved accessing the pulp chamber, irrigating copiously with sodium hypochlorite, applying a triple antibiotic paste as intracanal dressing, and then provisionally sealing it. After 3-4 weeks, the canal was cleaned and PRF was introduced in the canal that would serve as a scaffold for pulp revascularization. Mineral trioxide aggregate was used to seal the chamber and finally restored with composite. All the cases treated with PRF as a scaffold showed magnificant healing and apical end closure along with thickening of dentinal walls. On the basis of the results obtained in our case reports, we conclude that the revitalization of necrotic infected immature tooth is possible under conditions of total canal disinfection, and PRF is nearly an ideal biomaterial for pulp-dentin complex regeneration.